Psychological well-being of educators: Barriers, supports, and career development implications - Yuli Nurmalasari; Poh Li Lau (Jurnal Cakrawala Pendidikan, 2026)
Educator well-being has emerged as a critical determinant of both professional effectiveness and long-term career sustainability. Despite growing interest, the relationship between psychological well-being and educators' career development remains fragmented in the literature. This review synthesises empirical evidence from 13 peer-reviewed studies published between 2013 and 2024, identified through Scopus, Web of Science, and EBSCOhost, to examine how educators' psychological well-being influences career development, with a focus on key barriers, supports, and professional implications. The analysis shows that psychological well-being is positively associated with career engagement, job satisfaction, and resilience among teachers and school counsellors. Key personal factors, such as emotion regulation, self-compassion, and psychological flexibility, and organisational supports, such as collegial trust, administrative backing, and a collaborative work culture, were found to enhance well-being. Gender-based differences were also noted, with female educators often reporting higher well-being yet greater emotional sensitivity in high-stress contexts. Interventions combining individual-level strategies (e.g., mindfulness, acceptance and commitment therapy (ACT)) and systemic approaches (e.g., institutional support structures) were found to be most effective. This review underscores the need for multilevel interventions and cross-contextual research to inform inclusive and sustainable policies that enhance educator well-being across diverse educational settings.